Pyridine tetrafluoro-λ6-sulfanyl chlorides: spontaneous addition to alkynes and alkenes in the presence or absence of photo-irradiation. Issue 10 (23rd April 2020) - Niina, Kiyoteru; Tanagawa, Kazuhiro; Sumii, Yuji; Saito, Norimichi; Shibata, Norio
Abstract : A radical addition reaction of Py-SF4 Cl to alkynes and alkenes provide pyridine-SF4 -alkenes and pyridine-SF4 -alkanes under blue LED light irradiation or absence of light irradiation in CPME or without solvent. Abstract : An addition reaction of pyridine-tetrafluoro-λ 6 -sulfanylchlorides (Py-SF4 Cl) to alkynes and alkenes providing pyridine-tetrafluoro-λ 6 -sulfanyl-alkenes and pyridine-tetrafluoro-λ 6 -sulfanyl-alkanes is represented. The addition of Py-SF4 Cl occurs spontaneously in the presence of reactants, even in total darkness, but is affected in the presence of light. A series of SF4 -bridged pyridines were efficiently synthesized under a couple of environmentally benign conditions in good to high yields. The spontaneous reaction of Py-SF4 Cl is discussed based on the time-dependent analyses of the reaction in the presence or absence of photo-irradiation, and could proceed via a radical process.